Dynamic Gene Clusters Mediating Carbapenem-Resistant Acinetobacter baumannii Clinical Isolates - Samy Selim; Osama Ahmed Faried; Mohamed S. Almuhayawi; Osama A. Mohammed; Fayez M. Saleh; Mona Warrad (Antibiotics, 2022)
Acinetobacter baumanni (A. baumannii), a nonfermenting Gram-negative bacterium, has recently been associated with a broad range of nosocomial infections. To gain more meaningful insight into the problem of nosocomial illnesses caused by the multidrug-resistant (MDR) A. baumannii, as well as the factors that increase the risk of catching these infections, this investigation included a total of 86 clinical A. baumannii infections. Repetitive extragenic palindromic (REP)-PCR was used to investigate imipenem-resistant A. baumannii isolates for dynamic gene clusters causing carbapenem resistance. Four distinct A. baumannii lineages were found in the REP-PCR-DNA fingerprints of all isolates, with 95% of the samples coming from two dominant lineages. Imipenem, amikacin, and ciprofloxacin were less effective against genotype (A) isolates because of enhanced antibiotic tolerance. Lastly, to gain more insight into the mode of action of imipenem, we explored the binding affinity of imipenem toward different Acinetobacter baumannii OXA beta-lactamase class enzymes.